Business Actors' Default in K-Pop Merchandise Purchase Agreements on Social Media - Nastiti Respati Sedyo; Sulastri Sulastri (Universitas Muhammadiyah Sumatera Utara, 2026)
The rapid development of digital technology has transformed buying and selling transactions, including K-Pop merchandise trading through pre-order systems on social media. The pre-order system allows buyers to place and pay for orders before the goods are available. However, in practice, business actors often commit breaches of contract, such as delayed delivery, mismatched products, or unfulfilled refunds. This research aims to analyze the forms of breach of contract committed by business actors in K-Pop merchandise pre-order agreements and their legal consequences. The study uses a normative juridical method with a statutory and case approach, supported by literature review and data from real cases on social media platform X. The results show that business actors who fail to fulfill their contractual obligations are considered to have committed a breach of contract as stipulated in Article 1243 of the Indonesian Civil Code and are required to compensate the buyers for the losses. Dispute resolution can be pursued through both litigation and non-litigation means as regulated in Article 38 of Law Number 11 of 2008 concerning Electronic Information and Transactions.